Rozwiązać równania wielomianowe:       a) x3-2x2+x=0,    b) x3-3x2-9x+27=0.
​c)x3-5x2>0,   d) (x2-16)(x+3)(x-1)≤0.



Odpowiedź :

a)

x³-2x²+x=0

x(x²-2x+1)=0

x(x-1)²=0

x=0  ∨   x-1=0

x=0   ∨   x=1

x∈{0,1}

b)

x³-3x²-9x+27=0

x²(x-3)-9(x-3)=0

(x-3)(x²-9)=0

(x-3)(x+3)(x-3)=0

(x+3)(x-3)²=0

x+3=0  ∨  x-3=0

x=-3  ∨      x=3

c)

x³-5x² > 0

x²(x-5) > 0

x=0    ∨    x-5=0

x=0    ∨     x=5

x∈(5,∞)

d)

(x²-16)(x+3)(x-1) ≤ 0

(x+4)(x-4)(x+3)(x-1) ≤ 0

x+4=0  ∨   x-4=0   ∨   x+3=0   ∨   x-1=0

x=-4     ∨     x=4     ∨     x=-3     ∨     x=1

x ∈ (-∞,-4>∪<-3,1>∪<3,∞)